Global to local tensions in the production and enactment of Physical education curriculum policy reforms. Issue 2 (4th May 2019) - Paveling, Barry; Vidovich, Lesley; Oakley, Grace
ABSTRACT: This paper discusses the findings of a study on the production and enactment of physical education (PE) curriculum policy reforms in an Australian context. Over a decade, significant senior school reforms in Western Australia (WA) interacted with the introduction of an Australian Curriculum that rendered curriculum development dynamic and complex. A 'policy trajectory' was used to frame data collection and analysis from which a series of tensions was identified as having impacted on curriculum policy enactment in schools. These tensions, arguably, contributed to a growing loss of equity, which may have longer-term implications for future PE curriculum policy development.